Institutions of Stimulating the Innovative Behavior of Economic Agents in Khanty-Mansiysk Autonomous Okrug-Yugra: Evolution, Specificity and Institutional Traps - Islamutdinov, Vadim Faruarovich (International Journal of Economics and Financial Issues, 2016)
The purpose of research is identifying the evolution, specificity, and institutional traps of institutions of stimulating the innovative behavior of economic agents in Khanty-Mansiysk Autonomous Okrug – Yugra. As the methods of research author’s own classification of institutions, statistical analysis and comparative institutional analysis are used. The indices of innovation activity in the Khanty-Mansiysk Autonomous Okrug - Yugra were considered, the structure of institutions of stimulating the innovative behavior was specified, and the evolution of institutions of stimulating the innovative behavior in Russia and in Yugra was analyzed. The specificity of institutions of stimulating the innovative behavior in Yugra was revealed. Institutional traps in the sphere of stimulation of innovative behavior in Russia and in Yugra were defined. The prospects for the self-destruction of institutional traps under the action of external and internal factors were estimated. Possible ways of solution of institutional traps were offered. The results can be used by governments at the regional level as a basis for decision-making on the strategy and tactics of the development of the institutional environment to stimulate the innovative behavior of economic agents. Keywords: innovative activity, , Khanty-Mansiysk Autonomous Okrug - Yugra, evolution, specificity, institutional traps. JEL Classifications: D03, D23, D24